Conservative Management for Anterior STEMI Complicated by Ventricular Septal Rupture - Nanda Eka Sri Sejati; Habibie Arifianto; Irnizarifka - (PT. Kalbe Farma Tbk., 2019)
Ventricular septal rupture is a rare complication of acute myocardial infarction but with a very high mortality, most often caused by severe hemodynamic failure. Conservative treatment is very inefficient with over 90% mortality rate; surgery is recommended as definitive treatment. A case of 67-year-old woman with chest pain since 1 day accompanied by shortness of breath and diaphoresis. Cardiac auscultation showed a 3/6 systolic murmur without thrill. ST elevation at the anterior lead was found in ECG. Echocardiography detected a rupture in interventricular septal with left-to-right shunt. The patient was diagnosed with anterior ST elevation myocardial infarction (STEMI) complicated by ventricular septal rupture. A conservative management was given without intra-aortic balloon pump placement and surgical operation due to patient’s rejection. One month post treatment, the patient exhibited a relatively stable hemodynamic with moderate to severe activity limitation. Ruptur septum ventrikel merupakan komplikasi infark miokard akut yang jarang, namun mortalitasnya sangat tinggi, paling sering karena kegagalan hemodinamik berat. Penanganan konservatif sangat tidak efisien dengan tingkat kematian lebih dari 90 %; intervensi bedah direkomendasikan menjadi tatalaksana definitif. Seorang wanita 67 tahun mengeluh nyeri dada sejak 1 hari disertai sesak nafas dan diaforesis. Auskultasi jantung menunjukkan bising sistolik 3/6 tanpa thrill. EKG mendapatkan elevasi segmen ST di sadapan anterior. Pada ekokardiografi ditemukan ruptur septum ventrikel dengan left-to-right shunt. Pasien didiagnosis infark miokard akut elevasi ST anterior dengan ruptur septum ventrikel. Manajemen konservatif tanpa pemasangan intra-aortic balloon pump ataupun tindakan operatif karena pasien menolak. Satu bulan pasca perawatan, hemodinamik relatif stabil dengan keterbatasan aktivitas sedang-berat.